Mechanistic aspects of the H2-SCR of NO on a novel Pt/MgO−CeO2 catalyst - Efstathiou, Angelos M.; Costa, Costas (My University, 2007)
Steady State Isotopic Transient Kinetic Analysis (SSITKA) coupled with Temperature-Programmed Surface Reaction (TPSR) experiments, using on line Mass Spectroscopy (MS) and in situ DRIFTS have been performed to study essential mechanistic aspects of the selective catalytic reduction of NO by H2 under strongly oxidizing conditions (H2-SCR) at 140 Β°C over a novel 0.1 wt % Pt/MgOβ ’CeO2 catalyst for which patents have been recently obtained. The nitrogen paths of reaction from NO to N2 and N2O gas products were probed by following the 14NO/H2/O2 β†’ 15NO/H2/O2 switch (SSITKA-MS and SSITKA-DRIFTS) at 1 bar total pressure. It was found that the N-pathways of reaction involve two different in structure active chemisorbed NOx species, one present on the MgO and the other one on the CeO2 support surface. The amount of these active NOx intermediate species formed was found to be 14.4 ΞΌmol/g, corresponding to a surface coverage of ΞΈ = 3.1 (based on Pt metal surface) in agreement with the SSITKA-DRIFTS results. A large fraction of it (87.5%) was found to participate in the reaction path for N2 formation, in harmony with the high N2 selectivity (82%) exhibited by this catalyst. Inactive adsorbed NOx species were also found to accumulate on both Pt and support (MgO and CeO2). The mechanism of reaction must involve a H-spillover from the Pt metal to the support surface (location of active NOx species). It was proven via the NO/H2/16O2 β†’ NO/H2/18O2 (SSITKA-MS) experiment that gaseous O2 does not participate in the reaction path of N2O formation.
Keywords: Metals; Nitrogen oxides